The Charismatic Principle in Social Life. - Bruni, Luigino, 1966- (Routledge frontiers of political economy., 2012)
Max Weber laid the foundations for the meaning of 'charisma' in modern secular usage. This new volume argues for the importance of the 'charismatic principle' in history, economics and society. This volume brings together a number of contributors at the cross section between economics, theology, sociology and politics in order to set a research agenda for the following issues:What does it means to have a 'charism'? How does it work in society? How might one distinguish a 'charism' from a talent? Are 'charism's given only to ""special"" people, or are they also p.